2009
DOI: 10.1080/00365540802651897
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged impact of a one-week course of clindamycin on Enterococcus spp. in human normal microbiota

Abstract: Human intestinal Enterococcus spp. was monitored during a 2-y period after 7 d clindamycin treatment. Consecutive faecal samples were collected from 8 healthy volunteers, 4 of whom had received clindamycin. After treatment, the number of enterococcal colonies was diminished and species variation extended. Erythromycin and clindamycin resistance increased from 19% to 69% and 0% to 67%, respectively. Elevated resistance levels lasted up to 9 months and erm(B) was detected in samples up to 6 months. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Several studies have shown the adverse effects of different antibiotics on the host gut microbiota in both human subjects (54,58,135,171,304) and animal models (8,51,272,344). The aftermath of antibiotic administration often lasts for a long time after discontinuation of treatment (51,58,135,167,171), suggesting that a prolonged dysfunction is induced in the host's microbial "organ. "…”
Section: A Imbalance Leads To Chaosmentioning
confidence: 99%
“…Several studies have shown the adverse effects of different antibiotics on the host gut microbiota in both human subjects (54,58,135,171,304) and animal models (8,51,272,344). The aftermath of antibiotic administration often lasts for a long time after discontinuation of treatment (51,58,135,167,171), suggesting that a prolonged dysfunction is induced in the host's microbial "organ. "…”
Section: A Imbalance Leads To Chaosmentioning
confidence: 99%
“…In populations without underlying chronic diseases the selective pressure of prolonged antibiotic treatment can trigger a substantial reduction of metabolically important bacterial groups [1,2], favor selection of antimicrobial resistant strains [3] and decrease colonization resistance, eliciting overgrowth by potentially pathogenic microorganisms [4]. Moreover, several studies have reported a long-term post-treatment perturbation [5][6][7][8]. In young children, antibiotic-associated GI dysbiosis might have severe consequences for their quality of life by disturbing the maturation of the mucosa-associated lymphoid system [9][10][11][12] and inadequate immune development [13,14], thus increasing the risk for acquiring infections.…”
Section: Introductionmentioning
confidence: 99%
“…Shortterm changes in the quantity and composition of the bacteria comprising the normal human flora as a response to antibiotic exposure have been extensively recorded (for example Sullivan et al, 2001). However, only a few recent studies have investigated the long-term impacts of antibiotic administration, including development of resistance (Jakobsson et al, 2007;Jernberg et al, 2007;Lindgren et al, 2009;Löfmark et al, 2006;Nyberg et al, 2007;Sjölund et al, 2003).…”
Section: Impact Of Antibiotics On Normal Gut Microbiota Compositionmentioning
confidence: 99%